Damage to concrete bridges due to reinforcement corrosion: Part II-Design considerations - Kamaitis, Zenonas (Transport, 2002)
The mechanisms of reinforcement corrosion in concrete are the subject of extensive research. Although reliable methods for predicting the corrosive deterioration of concrete structures do not yet exist. This paper describes the durability problem of reinforced concrete bridges based on the mechanisms of carbonation depth or chloride profile. The deterioration model considering concrete carbonation, chloride penetration and concrete cover cracking is adopted to describe the service life of concrete structures. The corrosion models include environmental conditions, concrete carbonation or chloride diffusion rates, quality of concrete cover, steel corrosion rates and many other factors that make the predicting of service life of structures extremely difficult. Finally, the author gives the details of the methods of durabilio/verification and the proposals for its including in the national standards and practical guides.First Published Online: 19 Dec 2011